ADOPTION OF TELEMEDIC SERVICES IN MATERNAL AND CHILD HEALTH SERVICES - Natalia, Mega Silvia; Faraswati, Riska (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Maximum utilization of communication information technology in health services for maternal and children or recognized as telemedicine, is a friction in the model of providing midwifery care due to demands of the Covid-19 pandemic situation. There was obstacles in its use. The purpose of the study was to determine whether the factors of performance expectancy, effort expectancy, social influences, and facilitating conditions influenced behavioral intention to adopt telemedical system in the field of maternal and child health services by midwives through the Unifed Theory of Acceptance and Use of Technology (UTAUT). This a qualitative study used a survey method on 117 midwives in Probolinggo districts with simple random sampling as a sampling technique. Midwives were asked to fill out a questionnaire based on the four main constructs in UTAUT. Data were analyzed using multiples regression. The results of statistical test showed that only the effort expectancy variable had a positive relationship on the behavioral intention to adoption telemedicine system by midwife towards the provision of telemedicine health services (p value 0.001 < 0.05).